2016
DOI: 10.1177/1099800416659370
|View full text |Cite
|
Sign up to set email alerts
|

Extra Virgin Olive Oil Improves Oxidative Stress, Functional Capacity, and Health-Related Psychological Status in Patients With Fibromyalgia

Abstract: EVOO may protect women with FM against oxidative stress in addition to improving functional capacity and health-related psychological status. Findings suggest that olive oil may be a valuable therapeutic support in FM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…A large body of research [25][26][27] has proved that inflammation and oxidative stress play an important, adverse role in hepatic I/R injury. Recently, studies reported that supplementation with EVOO prevents oxidative stress [28,29]. As OA is one of the main components of EVOO, we explored the association between OA and EVOO.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research [25][26][27] has proved that inflammation and oxidative stress play an important, adverse role in hepatic I/R injury. Recently, studies reported that supplementation with EVOO prevents oxidative stress [28,29]. As OA is one of the main components of EVOO, we explored the association between OA and EVOO.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies reported weight or BMI outcomes, with no significant difference between interventions (Ramirez-Tortosa et al 1999, Vissers et al 2001, Moschandreas et al 2002, Machowetz et al 2008, Martin-Pelaez et al 2016, Rus et al 2016). Moreno-Luna et al 2012 reported that HPOO improved measures of endothelial function (asymmetric dimethylarginine, hyperemic area after ischemia, and total plasma nitrites/nitrates) in a hypertensive cohort.…”
Section: Other Measuresmentioning
confidence: 99%
“…Overall, the sample size of the included studies was relatively small; most studies included 10 to 49 participants, with the exception of the EUROLIVE cohort, which included 200 participants. Twelve studies recruited healthy adult participants while the remaining studies recruited specific populations (such as smokers (Moschandreas et al 2002) and post-menopausal women (Salvini et al 2006)) or participants with dyslipidemia, high blood pressure, fibromyalgia, and peripheral vascular disease (Ramirez-Tortosa et al 1999, Fito et al 2005, Visioli et al 2005, Fito et al 2008, Moreno-Luna et al 2012, Rus et al 2016.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations